District Government Communication Strategy in Improving Local Wisdom Tourism (Phenomenological Study of the Tanah Bumbu Government Tourism Office) - Moch Fauzi BT; Muzahid Akbar Hayat; Didi Susabto (Jurnal Multidisiplin Sahombu, 2025)
Local wisdom-based tourism is a strategic asset in regional development because it can provide economic benefits while maintaining cultural identity. This study aims to analyze the communication strategy of the Tanah Bumbu Regency Government, specifically the Tourism Office, in promoting local wisdom tourism. The study used a qualitative approach with a phenomenological method, involving eight key informants from government circles, tourism actors, and community leaders. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, presentation, and verification. The results show that the local government's communication strategy is implemented through three main forms: the use of social media (Facebook, Instagram, TikTok) to expand promotional reach; holding cultural festivals such as Aruh Ganal to attract tourists while preserving traditions; and multi-stakeholder collaboration with communities, the private sector, and local media to strengthen promotional networks. This strategy has been proven to increase public awareness, youth participation, and the number of tourist visits to local wisdom destinations. This study concludes that an adaptive, collaborative, and culturally value-based local government communication strategy can be an effective instrument in developing sustainable tourism. The practical implications are that strengthening human resource capacity, digital content innovation, and cross-sector collaboration governance are important prerequisites for the successful promotion of local wisdom tourism.